Enhancing Climate Resilience and Productivity in Cambodia's Mekong Delta Through Innovations in Rice-Field Ponds and Fisheries - Sean, Vichet; Wardell, David (WorldFish, 2024)
Rice-field fisheries (RFF) are vital to Cambodia's rural livelihoods and food security, but climate change and fluctuating resources require innovative approaches to maintain their effectiveness. The CGIAR Initiative on Asian Mega-Deltas (AMD), through Work Package 1, has introduced rice-field ponds as a key innovation to enhance the resilience and productivity of RFF. These ponds sustain fish populations during seasonal droughts and floods, providing crucial resources for household income and food security. By integrating fish and rice production, farmers secure food for their families and diversify their income sources, making their agricultural systems more adaptable to climate uncertainties.